Hypoglycemic effect of p-hydroxycinnamic diesters extracted from carnauba wax powder (Copernicia Prunifera) in alloxan-induced diabetic animals (Research, Society and Development, 2020)
Diabetes is a chronic non-transmissible disease and the number of cases is increasing every year. Plants appear as an alternative therapy since ancient civilizations. Among the species that have promising pharmacological activities are carnauba (Copernicia prunifera (Miller) H. E. Moore). Carnauba wax powder consists of a mixture of heterogenic compounds, among them, p-hydroxycinnamic diesters (HCA). Therefore, this study aimed to investigate the hypoglycemic effect of HCA in alloxan-induced diabetic animals. Therefore, this study was performed with 50 female Swiss mice, distributed in 5 groups (n = 10). The animals of the negative and positive control groups were treated with water: healthy and diabetic mice, respectively; animals of the HCA groups 25 and 50 were diabetic animals and they were treated with the HCA solution at doses of 25 and 50 mg / Kg, respectively; and with metformin, standard drug, at the dose of 200 mg / kg. After 28 days of HCA treatment, a significant hypoglycemic effect was observed in animals treated with HCA at the lowest dose tested (25 mg / kg). In the present study, HCA shown to be a promising compound with good scientific applicability due to the reduction of glycemia of diabetic animals induced by alloxan.